Peningkatan Laju Difusi Allisin dalam Sistem Fitosom Ekstrak Bawang Putih - Anisa Amalia; Rahmah Elfiyani; Adesi Chenia (Fakultas Farmasi Universitas Pancasila, 2021)
Garlic (Allium sativum L) contains allicin which has the property of reducing blood sugar levels. In previous studies, methanol extract of garlic can reduce blood sugar levels in mice at a dose of 400 mg/kg BW. Penetration of allicin can be increased by formulating extracts in the phytosome system. In this study, it will be observed the effect of making a phytosome system on the diffusion rate of allicin. Garlic extract phytosome was made using a thin layer hydration method which was then evaluated for its physicochemical properties which included testing of entrapment efficiency, density, particle size, index polydispersity, and zeta potential. Determination of the value of the diffusion rate of allicin in the extract and in the phytosome system was carried out using a modified diffusion cell for 420 minutes. The phytosome system formed has an entrapment efficiency value of 64.8789% with a density of 1.0051 g/mL, the particle size of 270 nm, the zeta potential of -32.55 mV and polydispersion index of 0.571. Diffusion rate testing indicates the diffusion rate of the phytosome system can increase the diffusion rate of allicin when compared to the diffusion rate of allicin in garlic extract.